Temperature Assessment of Heating Stage for a Thermoforming Equipment - Farah Amira, Mohd Ghazali; M. N., Ahmad; M. F., Ab. Rahim; Abdul Aziz, Jaafar (IOP Publishing, 2016)
Thermoforming is a well-known manufacturing process in the productions of various plastic household and industrial solutions. The heating of a plastic sheet allows the plastic to soften and within its forming window temperature the sheet can replicate a required shape when pressed against a mould. Hence, the heating process is an important thermoforming stage that determine uniformity of the material distribution. This article proposed an experimental approach to investigate the thermal characteristics of the heating section of a low cost thermoforming equipment designed for teaching and research purposes. The temperatures of air and a model of a stretched heated plastic sheet were measured and analysed. The experimental data indicates that the spatial temperatures distribution was not localised and the temperature history of the infrared heating agrees well with those given by fast response thermocouples. The findings suggest that the spatial uniformity of temperature can be reasonably evaluated by using the proposed method.